2015
DOI: 10.1007/s10549-015-3555-4
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of 21-gene recurrence score testing on early-stage breast cancer in Ireland

Abstract: The 21-gene test is a validated multi-gene diagnostic test that predicts chemotherapy (CT) benefit in oestrogen receptor positive (ER+), lymph node-negative (N0) breast cancer (BC) patients (pts). Ireland was the first public health care system to reimburse this test in Europe. Study objectives were to assess the impact of this test on decision-making and to analyse the economic impact of testing. Between October 2011 and February 2013, a national, retrospective, cross-sectional observational study of ER+, N0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…ODX was found to be a more accurate predictor of relapse than standard clinical features for individual patients [16]. Furthermore, ODX testing has been shown to result in cost-savings and a significant reduction in chemotherapy administration [7,17]. A metaanalysis by Carlson et al reported that ODX testing changed treatment decisions for 49% of the patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…ODX was found to be a more accurate predictor of relapse than standard clinical features for individual patients [16]. Furthermore, ODX testing has been shown to result in cost-savings and a significant reduction in chemotherapy administration [7,17]. A metaanalysis by Carlson et al reported that ODX testing changed treatment decisions for 49% of the patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…Disparity in staging and loss of information internationally will inevitably result from unequal access to biomarker studies. Within the more developed countries, variable access to multigene panels and economic considerations [40] will lead to differences in stage even with adoption of this new approach to BC. The availability of multiple genomic assays with varying concordance for individual patients is another confounding factor [41-45].…”
Section: Discussionmentioning
confidence: 99%
“…[9]. Prevention of chronic diseases could generate substantial savings on the healthcare budget, and make a positive impact on business and the economy, by prolonging healthy working life and reducing the impact of ill health on the labour market [10]. …”
Section: Time For a Further Leap In Healthcarementioning
confidence: 99%